Religion and nationalism in Chinese societies - Kuo, Cheng-tian 1957- (Amsterdam University Press, 2017)
This book explores the interaction between religion and nationalism in the Chinese societies of mainland China, Taiwan, and Hong Kong. Cheng-tian Kuo analyses the dominant religions, including Chinese Buddhism, Tibetan Buddhism, Daoism, Christianity, Islam, and folk religions, but he also goes beyond that, showing how in recent decades the Chinese state has tightened its control over religion to an unprecedented degree. Indeed, it could almost be said to have constructed a wholly new religion, Chinese Patriotism. The same period, however, has seen the growth of democratic civil religions, which could challenge the state
Keywords: Geschichte; Nationalisme; Gesellschaft; Nationalism; Nationalismus; Religion; RELIGION; Religious groups: social & cultural aspects; Religious groups: social and cultural aspects; Social groups; Society and culture: general; Society and social sciences Society and social sciences; Nationalism -- Religious aspects; Nationalism -- China; China; Hongkong; Taiwan; theology & religion; China / Religion / History; Chine / Religion / Histoire; Electronic books; History; Aufsatzsammlung